Community empowerment in using virgin coconut oil (LALAAN) as pruritus therapy - Diana Hardiyanti; Melinda Restu Pertiwi; Heryyanoor Heryyanoor (Universitas Muhammadiyah Magelang, 2022)
Virgin coconut oil (VCO) or lalaan oil is suspected to have non-pharmacological therapeutic benefits in pruritus. Community service activities in Sungai Tuan Ilir Village, Astambul District, Banjar Regency, South Kalimantan are carried out to empower the community to take advantage of the abundant coconut in the surrounding environment and to process it independently at home. The community service method is carried out by socializing health counseling, demonstrations and mentoring. This community service is able to improve the understanding and skills of the community in utilizing coconut as a non-pharmacological drug for the treatment of pruritus or itching. These skills can also be used as business opportunities for cadres and village communities by naming unique products, such as lalaan (lakas malawan gatalan).